Motivation to improve quality of university lecturers in Vietnam - Trung, Ngo Sy; Hai, Nguyen Duc; Tuyen, Nguyen Van (Edelweiss Applied Science and Technology, 2024)
Work motivation is one of the factors that greatly affects work results and efficiency, then the quality of human resources in an organization in general and human resources as university lecturers in particular. It has been confirmed by studies that work motivation includes both material factors (salary, bonus, monetary benefits) and spiritual factors (opportunities to develop professional and career capacity; rewards, honor). When an organization's human resources are cared for materially and spiritually, they will be satisfied and develop their working competence, contributing to the organization development. This study analyzes the work motivation of human resources with high professional qualifications, considered the quintessence of human resources - university lecturers. In terms of creating work motivation, in this study, two factors associated with the professional characteristics of lecturers are addressed on, including creating motivation to develop qualifications and teaching capacity and creating motivation to develop scientific research capacity; The impact of these two factors on the quality of university lecturers is specifically analyzed. Based on the theoretical framework, a survey was conducted with 150 lecturers from 3 public universities and 150 lecturers from 3 non-public universities to identify correlation between the creation of motivation in practice and quality of university lecturers in Vietnam. Findings suggests appropriate adjustments to policies so that Vietnamese lecturers’ quality could be encouraged to meet the development requirements of society.